Hepatocyte nuclear factor 4α regulates the expression of the murine pyruvate carboxylase gene through the HNF4-specific binding motif in its proximal promoter - Tanit Chavalit (2018)
Pyruvate carboxylase (PC) is the first regulatory enzyme of gluconeogenesis. Here we report that the proximal promoter of the murine PC gene contains three binding sites for hepatocyte nuclear factor 4α (HNF4α). These sites include the classical direct repeat 1 (DR1) (386/-374), non-perfect DR1 (-.118/-.106) and HNF4α-specific binding motif (H4-SBM) (-.26/-.14). Under basal conditions, mutation of the non-perfect DR1 decreased promoter activity by 50%, whereas mutation of neither the DR1 nor the H4-SBM had any effect. In marked contrast, only mutation of the H4-SBM decreased HNF4α-transactivation of the promoter activity by 65%. EMSA revealed that HNF4α binds to the DR1site and H4-SBM with similar affinity while it binds poorly to the non-perfect DR1. Interestingly, this non-perfect DR1 also coincides with two E-boxes. Mutation of the non-perfect DR1 together with the nearby E-box reduced USF1- but not USF2-transactivation of promoter activity, suggesting that USF1 partly contributes to the basal activity of the promoter. Substitution of the H4-SBM with the DR1 marginally reduced the basal promoter activity but did not eliminate HNF4α-transactivation, suggesting that HNF4α can exert its effect via DR1 within this promoter context. ChIP-assay confirmed that HNF4α is associated with the H4-SBM. Suppression of HNF4α expression in AML12 cells down-regulated PC mRNA and PC protein by 60% and 50%, respectively, confirming that PC is a target of HNF4α. We also propose a model for differential regulation of P1 promoter of PC gene in adipose tissue and liver. © 2013 Elsevier B.V.